Respon Petani terhadap Mekanisasi Pertanian pada Pertanian Padi di Kabupaten Penajam Paser Utara Provinsi Kalimantan Timur - Rina Dewi; Wawan Banu Prasetyo (Universitas Muhammadiyah Purworejo, 2022)
This study aims to determine the response of farmers to agricultural mechanization in rice farming and the factors that influence it. The basic method used is descriptive survey technique. Sampling of Penajam Paser (PPU) District location was determined purposively with consideration in the district, agricultural mechanization has penetrated to remote Penajam Paser Utara districts, be it transplants, hand tractors, hand tractors, R4 tractors, cultivators, power sprayers, hand sprayers, combine harvester, mobile RMU, and others. While the selection of farmers samples in Babulu and Penajam sub-district were determined by simple random sampling with a sample of 30 respondents. Data were analyzed by multiple linear regression analysis test. The results showed that most farmers have a high response to agricultural mechanization in rice farming cultivation. Factors that influence farmers' responses are the level of education, farming experience, land area, intensity of attending counseling, farmers' perceptions, and farmers' motivation. In this case the age of the farmer has no effect.